Despacho ótimo de potências ativa e reativa de sistema elétricos multi-áreas considerando restrições físicas, econômicas e ambientais =: Envronmentally constrained active-reactive optimal power flow-a compromising strategy for economic-emission dispatch and a multi-area paradigm - Kasmaei, Mahdi Pourakbari [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In a power system, the economic and emission dispatch and multi-area-based problems are considered as the two most challenging optimization problems. This work presents two novel mathematical models to address some drawbacks of the existing models in the domain of the aforementioned problems, including an economic and emission active- reactive optimal power flow (AROPF), and an integrated formulation for multi-area environmentally-constrained AROPF. In order to obtain an effective formulation to make an appropriate compromise between cost and emission, an unequivocal normalization-based paradigm (UNBP) is presented that solves the dynamic economic and emission AROPF problems. Unlike the commonly used methods, which are mostly applicable to simple OPF problems (economic dispatch, security-constrained economic dispatch, etc.), in the UNBP approach, rather than using a maximum output-based pollution control cost (MOPCC), an adaptive pollution control cost (APCC) is employed, which is a topology-based control cost is used. The main contribution of this paradigm is to make use of the normalization theory for the economic- oriented OPF, the environment-oriented OPF, and even for the APCC factor. In addition, in this work a multi-area active-reactive optimal power flow (MA- AROPF) is proposed. In the MA-AROPF model, instead of using decomposition methodologies that have several disadvantages and shortcomings, an integrated formulation that considers the environmental constraints is proposed. This integrated formulation has been created based on the concepts of centralized and decentralized models. This model can be easily solved via commercial solvers and because of its precise answer, it can be used in electricity markets, tie line planning, etc. In order to show the easy implementable characteristic of the MA-AROPF, it is applied on a tie line planning problem. In this work, in order to obtain optimal tie lines, the planning is performed under ...

Nos estudos de planejamento da operação de sistemas de energia elétrica a formulação e solução dos problemas de despacho econômico-ambiental e multi-área são considerados dois problemas de otimização desafiadores. Neste trabalho propõem-se dois novos modelos matemáticos que visam contribuir e contornar algumas desvantagens dos modelos existentes na literatura para os problemas de fluxo de potência ótimo ativo-reativo econômico- ambiental (FPOAREA), e uma formulação integrada para problema multi-área (FPOAREA- MA). No FPOAREA propõe-se uma formulação eficaz para obter um compromisso adequado entre os custos de geração e de emissão, através de um paradigma baseado em normalização inequívoca (PBNI). Ao contrário dos métodos comumente utilizados, que são principalmente aplicáveis a problemas de FPO simples (despacho econômico, despacho econômico com restrições de segurança, etc.), na abordagem PBNI, ao invés de usar um custo do controle da poluição com base na potência máxima (CCPBPM), utiliza-se um custo de controle adaptativo da poluição (CCAP), que representa o custo de controle baseado na topologia atual de operação da rede. A principal contribuição desse paradigma é utiliza a teoria da normalização para o FPO econômico-orientado, o FPO ambiental-orientado, e até mesmo para o fator CCAP. No modelo proposto para o FPOAREA-MA em vez de usar metodologias de decomposição descritas na literatura que têm várias desvantagens e problemas de coordenação, uma formulação integrada que considera as restrições ambientais é proposta. Esta formulação integrada foi desenvolvida com base nos conceitos de modelos centralizados e descentralizados. Este modelo pode ser facilmente resolvido através de solvers comerciais e a sua resposta é precisa, e os resultados obtidos podem ser usados em mercados de eletricidade, planejamento de linhas de interconexões entre sistemas vizinhos, etc. Para mostrar...
Keywords: Sistemas de energia eletrica - Planejamento; Energia eletrica - Transmissão; Energia elétrica - Distribuição; Otimização matematica; Electric power systems